2015
DOI: 10.1007/s12105-015-0615-3
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Sinonasal Non-Intestinal Type Adenocarcinomas are Truly Seromucinous Adenocarcinomas: A Morphologic and Immunophenotypic Assessment and Description of a Novel Pitfall

Abstract: While sinonasal intestinal type adenocarcinoma (ITAC) is defined by an intestinal phenotype, non-intestinal type adenocarcinoma (non-ITAC) is traditionally viewed as a diagnosis of exclusion, despite previous implication of a seromucinous phenotype and similarity to sinonasal seromucinous hamartomas (SSH). We performed a comparison of clinicopathologic and immunophenotypic features of ITAC, non-ITAC and SSH using traditional discriminatory markers and new markers of seromucinous differentiation. Twenty-three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Immunohistochemically, they are constantly positive for CK7, but usually negative for CK20 and CDX-2. Some 20 % of these tumors associate with sinonasal seromucinous hamartomas or respiratory epithelial adenomatoid hamartomas [ 39 , 41 , 42 ]. Due to positivity for markers of seromucinous differentiation such as DOG1, SOX10, and S-100, a subset of these carcinomas was called sinonasal seromucinous adenocarcinomas [ 42 ].…”
Section: Salivary-type Adenocarcinomasmentioning
confidence: 99%
“…Immunohistochemically, they are constantly positive for CK7, but usually negative for CK20 and CDX-2. Some 20 % of these tumors associate with sinonasal seromucinous hamartomas or respiratory epithelial adenomatoid hamartomas [ 39 , 41 , 42 ]. Due to positivity for markers of seromucinous differentiation such as DOG1, SOX10, and S-100, a subset of these carcinomas was called sinonasal seromucinous adenocarcinomas [ 42 ].…”
Section: Salivary-type Adenocarcinomasmentioning
confidence: 99%
“…One previous case tested for DOG-1 [10] was reportedly negative, but here it is positive along with SOX-10. DOG-1, a calcium dependent chloride channel, demonstrates moderate apical staining in the sinonasal seromucinous glands [14,15]. Similarly SOX-10 is strongly expressed insinonasal glands [14].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the histogenesis of SRCLC remains uncertain. New markers for seromucinous glands, including sinonasal glands, namely DOG1, SOX10 and S100 have been defined [ 20 , 21 ]. DOG1, a calcium-activated chloride channel, initially described in gastrointestinal stromal tumors, but now known to be expressed in normal sinonasal seromucinous glands, it shows moderate apical luminal staining of serous acini with weaker staining in mucous acini.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that tumor cells in SRCLC are positive for two of these three seromucinous markers, suggesting possible seromucinous derivation of SRCLC. It has also been reported that markers of seromucinous differentiation are present to varying degrees in the majority of low-grade non-intestinal-type adenocarcinomas [ 21 ]; a term which has been used synonymously with renal cell -like carcinoma (SRCLC) in the new edition of WHO classification of head and neck tumors [ 22 ]. With a common seromucinous phenotype, we conclude that SRCLC is likely a clear cell variant of sinonasal non-intestinal type adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%